Structure and magnetic properties of Ni-N nanofilms - Shalayev, R.V.; Prudnikov, A.M.; Kutrovskaya, S.V.; Varyukhin, V.N.; Linnik, A.I.; Arakelian, S.M. (Functional Materials, 2014)
All range of nanostructured films of nickel nitrides is synthesized by the method of magnetron sputtering (from the phase of Ni and up to the phase of Ni₂N) and was investigated the change in the magnetic properties. We found out the globular structure of paramagnetic phases of Ni₃N and Ni₂N, and also the ferromagnetic behavior of Ni₄N phase is confirmed.